“Perimetri” di sistema. Riflessioni e critiche sul mondo dell’asilo in Italia - Segneri, Maria Concetta; Gatta, Rosaria (EtnoAntropologia, 2016)
Authors describe, through a multidisciplinary model, the needs of applicants/beneficiaries, of international protection. Particularly, how their health narratives are correlated with the lack of suitability of the Italian asylum system. From experience at NIHMP mental health clinic since 2011, they used the ethnography method to highlight the connection between the issues observed in Italian forced migration policy and the experiences of suffering, violence, alienation, and helplessness lived by both patients and health workers.